Electrical Behavior of an Ultralow-Energy Plasma-Focus Device - Barbaglia, Mario Oscar (2014)
Measurements of electrical signals in discharges performed in a miniature plasma-focus device (5 nF capacitor bank, central electrode diameter and effective free length 2.0 and 0.5 mm, respectively, no outer electrode) are reported. A lumped  model is built that gives good agreement between the model and the recorded signals. The main conclusions are as follows: the voltage at which the chamber disk capacitor is charged is limited by the gas filling pressure inside the chamber and not just by the voltage in the capacitor energy source, and the behavior of the discharge current within the vacuum chamber depends on the whole system and not only on the last portion of the circuit, even for longer transmission line lengths.